Food substitution models for nutritional epidemiology. Issue 2 (9th December 2020) - Ibsen, Daniel B; Laursen, Anne Sofie D; Würtz, Anne Mette L; Dahm, Christina C; Rimm, Eric B; Parner, Erik T; Overvad, Kim; Jakobsen, Marianne U
ABSTRACT: The advantage of using specified substitution analysis in nutritional epidemiology has been clearly demonstrated in studies of macronutrient intake and disease risk. However, the method has not been widely applied in studies of food intake. The aim of this article is to describe and compare the interpretation and application of different food substitution models in epidemiologic studies on diet and disease development. Both theoretically and in the context of a specific example, we discuss methodologic issues to be considered, including modeling of food substitutions using diet at a single time point or at multiple time points (focusing on dietary changes), choice of substitution unit, adjustment for total energy intake, and adjustment for confounding. We argue that specified food substitution analyses can be used to identify optimal food composition of the diet and that these analyses are thus highly relevant to inform public health policy decision makers.